Pengaruh Green Creativity terhadap Green Competitive Advantage dengan Mediasi Green Brand Image - Ramadhani Abanan, Muchammad Zuhri; Isharina, Ikhtiara Kaideni (Penerbit Goodwood, 2024)
Purpose: This study explores the influence of green creativity on green competitive advantage in Surabaya's logistics industry, with green brand image as a mediator. With Indonesia's logistics sector facing urgent environmental challenges, sustainable innovations, and enhance a company’s eco-friendly image.Methodology: A quantitative approach was used. Data was gathered from 140 member companies of the Indonesian Trucking Association (Aptrindo) DPC Surabaya, with top management as respondents. A census sampling method was used, and the data was analyzed through Structural Equation Modeling (SEM) using a Partial Least Square (PLS) approach.Results: The findings show that green creativity positively affects both green competitive advantage and green brand image. Additionally, green brand image enhances green competitive advantage and mediates the relationship between green creativity and competitive advantage.Conclutions: To achieve sustainable competitive advantage, companies in the transportation sector need to continue to innovate through green creativity and build a strong green brand image. In doing so, companies will not only improve their brand image in the eyes of consumers but also strengthen their competitiveness in the increasingly competitive and sustainability-oriented logistics industry.Limitations: The study has limitations, including its focus on members of the Indonesian Trucking Association DPC Surabaya and the transportation sector.Contribution: Despite these limitations, it offers valuable insights for entrepreneurs, government bodies, investors, and academics aiming to promote sustainability in logistics and other sectors.